Risk-sharing and the creation of systemic risk - Viral V. Acharya; Aaditya M. Iyer; Rangarajan K. Sundaram (Journal of Risk and Financial Management, 2020)
We address the paradox that financial innovations aimed at risk-sharing appear to have made the world riskier. Financial innovations facilitate hedging idiosyncratic risks among agents; however, aggregate risks can be hedged only with liquid assets. When risk-sharing is primitive, agents self-hedge and hold more liquid assets; this buffers aggregate risks, resulting in few correlated failures compared to when there is greater risk sharing. We apply this insight to build a model of a clearinghouse to show that as risk-sharing improves, aggregate liquidity falls but correlated failures rise. Public liquidity injections, for example, in the form of a lender-of-last-resort can reduce this systemic risk ex post, but induce lower ex-ante levels of private liquidity, which can in turn aggravate welfare costs from such injections.
Keywords: G21; G22; G31; 330; banking; clearinghouses; systemic risk; Finanzprodukt; Risikomanagement; Systemrisiko; Bank; Clearing; Lender of Last Resort